Analisis Peran Guru dalam Mengungkapkan Kemampuan Komunikasi Siswa Tunarungu di Kelas VI SLB-B Karya Murni Medan - Muthia Aprilianty (Scholarly Journal of Elementary School, 2026)
This study aims to analyze the role of teachers in developing the communication skills of deaf students in Grade Six of Karya Murni Special Needs School, Medan. This study used a qualitative approach with descriptive methods. Data collection techniques were conducted through observation and interviews with homeroom teachers as key informants. The results indicate that teachers play a crucial role as facilitators and mediators in developing the communication skills of deaf students through the use of sign language, visual media, and intensive direct interaction. Teachers also implement various strategies such as total communication, the use of visual learning media, and repetition of material to facilitate student understanding. However, several obstacles are encountered, including limited student vocabulary, differences in communication ability levels, and learning that tends to be general and repetitive. Therefore, the development of more innovative, adaptive, and individual-needs-based learning strategies is needed to optimally improve communication skills.